Hubungan Dukungan Psikososial Dengan Kepatuhan Minum Obat Pasien TB Paru Di RS Royal Prima Medan - Ziraluo, Darniwati; Buulolo, Arisman; Halawa, Afeus; Ferdiansyah Sitopu, Robin; Basri, Basri (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
Tuberculosis (TB) is an infectious disease affecting the lungs caused by the bacterium Mycobacterium tuberculosis. This study aims to determine the relationship between psychosocial support and medication adherence in pulmonary TB patients during treatment. This quantitative study used a cross-sectional design. The sampling technique used was a total sampling of 30 participants. Data were collected using a questionnaire containing items related to psychological support, social support, and medication adherence. Data were analyzed using univariate and bivariate analyses. Univariate analysis was used to distribute the frequencies of the study variables, while bivariate analysis used the Chi-square test to determine the relationship between variables. The results showed a significant relationship between psychological support and medication adherence (p-value = 0.001), as well as between social support and medication adherence (p-value = 0.001). In conclusion, there is a relationship between psychological and social support and medication adherence in pulmonary TB patients. Hospital management is recommended to improve education, especially for patients’ families, to provide optimal support to family members with TB.